A first record of Pestalotiopsis clavispora in Argan mass cutting propagation: Prevalence, prevention and consequences for plant production - Bakry, Mustapha; Bussières, Guy; Lamhamedi, Mohammed; Margolis, Hank; Stowe, Debra; Abourouh, Mohamed; Blais, Martine; Bérubé, Jean (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
A trial involving the mass propagation of Argania spinosa cuttings was established following two protocols: in mini-bouturathèques without mist and in a greenhouse under mist. Symptoms of petiole necrosis, foliar yellowing and abundant black acervuli were observed under both protocols. These symptoms were responsible for a 90% mortality rate in the mini-bouturathèques while under the mist treatment premature fatal necrosis of the apical buds resulted in 100% mortality. The disease’s causal agent, Pestalotiopsis clavispora, was identified on the basis of its morphological characteristics and by molecular analysis. Alternating weekly treatments of systemic and contact fungicides resulted in a 41% success rate in controlling this pathogen, described for the first time on argan cuttings.